ANALISIS STRATEGI PENGEMBANGAN USAHA TAS RANSEL DI CV. RIFKY ARAFA DENGAN MENGGUNAKAN METODE SWOT DAN QSPM - Akbar Nugraha; Dedy Khaerudin; Isnaini Mahuda (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
CV. Rifky Arafa is a type of micro, small and medium enterprise (UMKM) which is engaged in the convection sector. Located in Kadugenep, Kab. Serang-Banten, it is also included in the center of the bag industry because the majority of the population are bag craftsmen. The beginning of this business was founded in 1997 by Bpk. H. Rohman’s and his brother, he used to work as a convection tailor in Jakarta. One year later, coinciding with the 1998 monetary crisis, caused many convection businesses in Jakarta to go bankrupt so that the migrants from Kadugenep Village automatically returned to their hometowns. The purpose of this research is to find out how the results of the analysis of business development strategies that must be carried out by CV. Rifky Arafa best done. And what are the results of the analysis using the SWOT and QSPM methods. The analysis used to formulate the strategy is the IFE matrix, EFE matrix, IE matrix, SWOT matrix and QSPM. Internal factors that influence the strength factor in developing a backpack business are three factors with the highest value, namely quality products, maintaining the quality of raw materials well, and CV. Rifky Arafa already has a business license (0.395), from the weakness factor, namely the need for additional capital costs to develop a business, especially CV. Rifky Arafa (0,129). While the external factors that influence the opportunity factor are the need to use sophisticated machines to increase production (0,603), and the threat factor is the increase in market demand in a certain month (0,235). CV. Rifky Arafa is in a position (growth and build) or grows and develops with IFE (3,161) and value of EFE is (3,066). The largest TAS value with a value of 8,000 is the need for work motivational guidance to its employees, and also the need for additional costs to develop a business in the bag industry center, especially on CV. Rifky Arafa